KEPEMIMPINAN TRANSFORMATIF ABAD 21 DALAM MEMAKNAI PROBLEMATIKA DEMOKRASI - Yulius Rustan Effendi; Didik Iswahyudi; Samapati, Cevin (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2024)
Transformative leadership as a paradigm that continues to develop in the context of the 21st century offers unique thinking in understanding and responding to various challenges related to democracy today. This article aims to investigate the role of transformative leadership in interpreting and overcoming various problems that arise in the context of democracy in student organizations. Through transformative leadership, this article offers a solution based on empowerment, active participation, and building member capacity. Transformative leadership encourages the creation of an inclusive environment where individuals have avoice that is valued and heard. This creates a strong foundation for resolving conflict, strengthening trust, and promoting ongoing engagement. Thus, this article concludes that transformative leadership has great potential to become a facilitator in dealing with democratic problems in the contemporary era. Through this approach, it is hoped that student organizations can build a stronger foundation for an inclusive, dynamic and sustainable democracy.